Faktor-Faktor Yang Mempengaruhi UMKM Untuk Menggunakan QRIS Sebagai Metode Pembayaran Dalam Proses Akuntansi - Edya Nashwa Septika; Aqilah Miranda; Yohanes Kevin Lukna; Citra Amelia Parsi; Riska Franita (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study wants to analyze the factors (perceived usefulness & perceived ease of use) that influence interest in using QRIS for UMKM in Medan. Researchers used 40 UMKM as subjects which were obtained purposively. Data collection was carried out by distributing questionnaires directly & online, the data was analyzed with Multiple Regression. The results show that Interest in Use is influenced by Perceived Usefulness and Perceived Ease of Use.